Trace metals in Thais clavigera along coastal waters of the East Coast of Peninsular Malaysia - Miskon, Mohd Fuad; Mohamad Shazili, Noor Azhar; Mohammad, Faridah; Yunus, Kamaruzzaman (Penerbit UKM, 2014)
The selected trace metals in the soft tissue of Thais clavigera from 11 sampling sites along the coastal waters of the east coast of Peninsular Malaysia were studied. Significant inter-spatial variations in trace metals were recorded. Sites with relatively high concentrations of the contaminant metals Hg, Cd, Pb and Zn are correlated to their close proximity to industrial and urban sites or to boating and aquaculture activities. This could possibly be contributed by the high growth of industrial activities like port and sewage release. Interspatial comparison with previous studies indicated lower measurement. Meanwhile, comparison with other studies around the world also designated lower values except for Zn. The metal accumulation patterns indicated an enrichment of essential metals over non-essential metals. Comparison of metal concentration with maximum permissible limits of toxic metals in food established in different countries, as well as Malaysian Food Act 1983 and Food Regulations 1985 Fourteen Schedule, indicated the values were well within safety levels.